Cumulative risk and newly qualified teachers' professional well-being: Evidence from rural Ghana. (December 2020) - Fatima, Syeda Farwa; Wolf, Sharon
The transition from student-teaching to full-time teaching is an understudied period in teachers' careers. This paper uses a cumulative risk (CR) framework to assess personal and professional risks experienced by 135 student-teachers in rural Ghana during pre-service training and later as newly qualified teachers, and examines how risks relate to their professional well-being and learning outcomes of children in their classrooms. Higher CR was associated with lower teacher motivation and personal accomplishment. Furthermore, higher CR predicted lower child numeracy skills and socioemotional development over the school year. Implications for teacher professional development and improving educational quality are discussed.